University Students' Self-Directed Approach to Learning a Foreign Language - Zohidova M.F. (Global Scientific Publishing, 2024)
The article explores the main difficulties in promoting independent learning for students in non-language fields, especially when it comes to teaching foreign language communication. Independent study in foreign language education in higher professional education is seen as a way to gain a deep understanding of professional knowledge and cognitive methods. The author has examined theoretical approaches and learned from Russian and international teaching experiences. The methodological and organizational aspects of this issue were examined and outlined systematically. Considering current circumstances, the educational potential of combining traditional and distance learning for organizing students' independent work is also discussed
Keywords: Extensive language material; the development of critical thinking